Collaborative Governance of MSMEs On Legal Protection for Online Transactions During the Covid19 Pandemic - Agani, Muh Hasbi Azis; Abadi, Ahmad Takbir; Muhiddin, Amir; Handam, Handam (Universitas Muhammadiyah Yogyakarta, 2021)
The Covid-19 pandemic affects many aspects of people's lives, particularly the economic component, which is so important. During the Covid-19 epidemic, large-scale social restriction legislation made it impossible for MSME actors in the production process to market their products, resulting in a fall in revenues. The evolution of globalization and the use of the internet necessitates a shift in habit from traditional sales to e-commerce, which is being used by MSME actors to survive the Covid 19 pandemic. E-commerce marketing can assist MSME actors in running their businesses efficiently and practically without being constrained by distance and space. Secondary data from journals, academic reports, books, and the outcomes of past research on SMEs is used in this qualitative study. The government's attitude toward ensuring security in online transactions is examined in this study, which focuses on MSMEs that were affected by large-scale social restrictions and social isolation during the Covid19 pandemic. The conclusion reached is that the government, in this case as a policymaker, has provided legal clarity to protect consumers who transact through online media with Law Number 8 of 1999 concerning Seller's Rights, which has been properly regulated so that sellers feel safe from fraud when transacting. There is still a need to focus on the government's role in enabling the issue of procedures for electronic registration and publication of trading enterprises.